Bleeding risk with clopidogrel and percutaneous endoscopic gastrostomy - Sohail, Umair (World J Gastrointest Endosc, 2016)
AIM: To compare bleeding within 48 h in patients undergoing percutaneous endoscopic gastrostomy (PEG) with or without clopidogrel. METHODS: After institutional review board approval, a retrospective study involving a single center was conducted on adult patients having PEG (1/08-1/14). Patients were divided into two groups: Clopidogrel group consisting of those patients taking clopidogrel within 5 d of PEG and the non-clopidogrel group including those patients not taking clopidogrel within 5 d of the PEG. RESULTS: Three hundred and nineteen PEG patients were found. One hundred and sixty-eight males and 151 females with mean body mass index 28.47 ± 9.75 kg/m(2) and mean age 65.03 ± 16.11 years were identified. Thirty-three patients were on clopidogrel prior to PEG with 286 patients not on clopidogrel. No patients in either group developed hematochezia, melena, or hematemesis within 48 h of percutaneous endoscopic gastrostomy (PEG). No statistical differences were observed between the two groups with 48 h for hemoglobin decrease of > 2 g/dL (2 vs 5 patients; P = 0.16), blood transfusions (2 vs 7 patients; P = 0.24), and repeat endoscopy for possible gastrointestinal bleeding (no patients in either group). CONCLUSION: Based on the results, no significant post-procedure bleeding was observed in patients undergoing PEG with recent use of clopidogrel.